2023
DOI: 10.1055/a-2037-6323
|View full text |Cite
|
Sign up to set email alerts
|

National Inpatient Datasets May No Longer Be Appropriate for Overall Total Hip and Knee Arthroplasties Projections after Removal from Inpatient-Only Lists

Abstract: Introduction: It is unknown if the National Inpatient Sample (NIS) remains suitable to conduct projections for total knee (TKA) and hip arthroplasty (THA), after their removal from “Inpatient Only Lists” in 2018 and 2020, respectively. We aimed to: (1) quantify primary THA and TKA volume from 2008 to 2018; (2) project estimates of future volume of THA and TKA until 2050; (3) compare projections based on NIS data from 2008-to-2018 and 2008-to-2017, respectively. Methods: We identified all primary THA and TKAs p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The future demand for TJAs was estimated by reviewing the NIS database [16][17][18] to obtain the number of THAs and TKAs performed from 2008 to 2017 (see Appendix Table A1). The International Classification of Diseases, Ninth and Tenth Revision (ICD-9 and ICD-10) codes specific for primary THA and TKA were used to identify procedures.…”
Section: Projected Tja Volumementioning
confidence: 99%
“…The future demand for TJAs was estimated by reviewing the NIS database [16][17][18] to obtain the number of THAs and TKAs performed from 2008 to 2017 (see Appendix Table A1). The International Classification of Diseases, Ninth and Tenth Revision (ICD-9 and ICD-10) codes specific for primary THA and TKA were used to identify procedures.…”
Section: Projected Tja Volumementioning
confidence: 99%
“…This paper specifically focuses on CPSP related to total knee arthroplasty (TKA) surgery. In the United States, total knee arthroplasty is one of the most performed orthopedic surgeries, with approximately 480,000 primary TKAs performed in 2019 and projections estimating between 800 thousand and 1.2 million TKAs annually in the 2040s/50s [17,18]. Studies have shown a high satisfaction rate in post-TKA patients (70-88%) based on pain reduction and functional improvement, and patients are often recorded as making notable progress in function and pain reduction between 3 to 6 months post-surgery [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…2 Recent estimates project this growth to continue, 3 models from different periods estimate approximately 0.8 and 1.0 million TKA cases by 2050 in the United States. 4 In China, a recent report showed the case number of TKA increased from 53,880 in the year 2011 to 374,833 in the year 2019, with a dramatic 5.9-fold increase. 5 However, despite being a mature technique, TKA has postoperative complications including pain, wound oozing, and infection.…”
Section: Introductionmentioning
confidence: 99%
“…With the population aging, the annual number of TKAs performed has markedly increased 2 . Recent estimates project this growth to continue, 3 models from different periods estimate approximately 0.8 and 1.0 million TKA cases by 2050 in the United States 4 . In China, a recent report showed the case number of TKA increased from 53,880 in the year 2011 to 374,833 in the year 2019, with a dramatic 5.9‐fold increase 5 …”
Section: Introductionmentioning
confidence: 99%